O direito educacional da pessoa com deficiência - SILVA, Petison Teixeira da (2024)
The objective of this study is to do a reflection about the factors that contribute to the inclusion of students with disabilities don’t work in school practice. The Bibliographic material used in this study, was selected according to the theme, Mantoan (2003), Candau (2008, 2013), Monetto (2010), among others. Considering what Brazilian legal documents for people with disabilities defends, including the Federal Constitution (1998), Law of Directives and Bases of National Education (1996) and Brazilian Law inclusion (2015), among others. It’s possible to realize that the actions for the inclusion of people with disabilities in regular education class are described in current Brazilian legislation. However, it is noticed that student with disabilities are still excluded in the school environment and in the regular classroom. There are countless factors that contribute for this, school’s infrastructure, with the accessibility necessaries, such as ramps, tactile floor, and informative boards with Brazilian sign language (LIBRAS). The curriculum still appears as an obstacle to the inclusion, because it is not designed and materialized to meet the needs of these students. There are also behavioral obstacle in the relationships stablished in the face of disability. Which culminate in the exclusion of the student from the activities developed inside and outside of the classroom.